Tariff Bindings, Unused Protection and Agricultural Trade Liberalisation - Walkenhorst, Peter (OECD Publishing, 2003)
Prior quantitative assessments of the effects of agricultural trade liberalisation have assumed that negotiated reductions in bound tariffs translate into corresponding cuts in applied tariff rates. This approach, however, overestimates the actual reduction in applied tariffs and, hence, the benefits of trade liberalisation, since applied rates are often much lower than the tariffs bound in Uruguay Round schedules. This paper uses data on applied and bound tariffs and the GTAP-CGE model to quantify the magnitude of the resulting bias. The findings suggest that the distortion of estimates is particularly pronounced for modest tariff cuts, as well as for countries where the differences between bound and applied rates are substantial. Hence, quantitative policy analysts who aim to inform decision makers on the likely impacts of negotiated tariff cuts should consider the relationship between bound and applied tariff rates in their assessments in order to avoid mistaken advice...